1986
DOI: 10.1002/aic.690320909
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of sodium bicarbonate decomposition

Abstract: A thermal gravimetric method was used to measure rates of decomposition of NAHCO, particles. Such decomposition produces a highly porous Na,Co, that reacts with SO, rapidly and completely at moderate temperatures. Hence, NaHCO, decomposition provides a reactant with attractive features for SO, removal. The rapid rate of decomposition combined with the high heat effect prevented determining intrinsic rates by constant temperature runs when the temperature level was above 400 K. However, rising-temperature runs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
2
4

Year Published

1987
1987
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 12 publications
5
26
2
4
Order By: Relevance
“…It seems meaningful to compare the present results with those obtained under the condition comparable with the present one, in particular with a smaller sample size. The values of E obtained compare with those reported by Van Dooren and Mueller [13] and Hu et aL [1].…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…It seems meaningful to compare the present results with those obtained under the condition comparable with the present one, in particular with a smaller sample size. The values of E obtained compare with those reported by Van Dooren and Mueller [13] and Hu et aL [1].…”
Section: Resultssupporting
confidence: 83%
“…As for the kinetic obedience, the first order (F1) law was observed by Hu et al [1]. This is not necessarily contradictory to the present result because the F 1 law was not markedly inferior and the exponent m in the A m function was extended to nonintegral values between unit and four to find the better linearity [10].…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Active sodium carbonate is obtained by the decomposition of sodium bicarbonate (Wang Hu et al, 1986;Subramanian et al, 1972). The overall kinetics of the reaction of SO, with Na2C0, has also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The BET surface areas and the pore specific volumes of Na 2 CO 3 , measured with a Carlo Erba Sorpotomatic 1900, were 3.38×10 3 m 2 kg −1 and 3.11 × 10 −4 cm 3 g −1 , and 3.78 × 10 3 m 2 kg −1 and 6.21 × 10 −3 cm 3 g −1 for the 120 and 209 m sorbent, respectively. As reference, Hu et al (1986) reported, for particles of NaHCO 3 of 125 m diameter decomposed at 100 • C to Na 2 CO 3 , a specific surface area of 3.3 × 10 3 m 2 kg −1 .…”
Section: Methodsmentioning
confidence: 98%